INTERNAL CONTROL OF ACCOUNTS RECEIVABLE THROUGH COMPUTER SYSTEMS IN LOCAL GOVERNMENTS YEAR 2023 - Morante Narváez, Manuel Eduardo (2026)
Objective: To explain the effect of the non-application of the Siaf Rents Cadastral Income Module on the collection management of Directly Collected Resources (RDR) by Municipalities, proposing how to include the aforementioned module in the official SIAF software so that income is controlled, ensuring that accounts receivable are reflected in the Financial Statements; the actual balances of accounts receivable, and their corresponding provision in accordance with Accounting Principles and Standards, Financial Reporting, and International Control Standards. Method: The research has been qualitative, empirical, descriptive, correlational or explanatory, using the inductive and pragmatic methods for the conclusions. Results: It shows the importance of transferring the accounting movement of receivable and their provision to the SIAF en línea, to safeguard Internal control of the accounts, period 2023, Conclusion: The SIAF Software should be used integrally whit the Cadastral Income Module to improve collection and control current accounts, suggesting that cadastral survey to form the database.